2019
DOI: 10.31025/2611-4135/2019.13819
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Application of Gis in Biomass and Solid Waste Supply Chain Optimization: Gaps and Opportunities for Developing Nations

Abstract: The application of Geographical Information Systems (GIS) enhanced modelling techniques in biomass and solid waste supply chain problems is hinged on a common denominator for both systems: the spatial distribution of supply points and variability of resource quantities. Since the sustainability of bioenergy or waste-to-energy projects around these resources will be affected significantly by the cost of supplying them, it is important to optimize decisions around facility location, size and transport routes. GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several previous studies have identified GIS as a suitable and versatile tool to perform the spatial analysis needed for the location of a biomass power plant and of the related biomass supply chain [23,39,40]. Through this technology, it is indeed possible to capture, store, analyze, display and manipulate spatial data [41], also integrating them with non-spatial quantitative or qualitative data [23]. Considering this, much attention has been paid to such tools by scientific research in the renewable energy sector, with a particular focus on energy from biomass.…”
Section: Recent Gis Applications In Spatial Allocation Of Biomass Powmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have identified GIS as a suitable and versatile tool to perform the spatial analysis needed for the location of a biomass power plant and of the related biomass supply chain [23,39,40]. Through this technology, it is indeed possible to capture, store, analyze, display and manipulate spatial data [41], also integrating them with non-spatial quantitative or qualitative data [23]. Considering this, much attention has been paid to such tools by scientific research in the renewable energy sector, with a particular focus on energy from biomass.…”
Section: Recent Gis Applications In Spatial Allocation Of Biomass Powmentioning
confidence: 99%
“…Certainly, the degree of the sustainability of a given biomass plant depends on several factors, such as: a regular and consistent biomass availability, well-designed logistics of feedstock supply, and optimal use of the resources [18][19][20][21]. Particularly, the location of the power plant is critical [22] and the Geographic Information System (GIS) is one of the most powerful and widely accepted tools for planning in agriculture and forestry sectors [23][24][25][26]. In fact, GIS permits us to combine both spatial and non-spatial factors such as the extractable biomass from forests and orchards, cost indicators and particular restrictions applied on a given area [27][28][29] to assess land suitability for the location of the biomass plant [30][31][32] and support the decision-making phase of the whole supply chains [19,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…According to Charis et al [48], problems of BSC and the management of urban solid waste share a "common denominator": both depend on the spatial distribution of supply points and variability in the quantity of resources. The authors pointed out that GISs are an important tool that can be used to capture the spatiotemporal dynamics of biomass and waste.…”
Section: Geographic Information Systems-gissmentioning
confidence: 99%
“…During the last decades, the use of Geographic Information Systems (GIS) for agriculture and forestry planning has gained interest for the vast panorama of possible applications [9][10][11]. The most interesting feature is combining spatial and non-spatial information to facilitate decision-making, for instance, in feedstock supply chains or FMP [12].…”
Section: Introductionmentioning
confidence: 99%